The Reaserch of Dry Chicken Manure Methanogenesis Stability - Shapovalov, Yevhenii; Salyuk, Anatoly; Kotynskyy, Andriy; Tarasenko, Roman (My University, 2019)
The studies were conducted in batch mode in thirteen repetitions at humidity of 78, 80, 82 and 84%. The coefficient of variation of methane production varied from 14.84% to 35.17% in a mesophilic mode and from 14.4% to 78.21% in a thermophilic mode, which means high instability of the process. The moisture content had a much greater effect on the stability of the process in thermophilic conditions than in mesophilic ones.
Keywords: кафедра харчової хімії; adaptation; адаптація; biogas production; виробництво біогазу; dry fermentation; суха ферментація; methane fermentation; метанова ферментація; methanogenesis; метаногенез; кафедра екології та екоменеджменту